Qualifications and Competencies of Guidance Designates, and Extent of Implementation of School-Based Guidance Services: Insights for Capacity-Building Initiatives - Dumlao-Tafalla, Charlene (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the professional qualifications and competencies of guidance designates and the extent of implementation of school-based guidance services in public secondary schools in the second congressional district of Northern Samar. Anchored on Social Cognitive Theory, Systems Theory, Competency-Based Theory, and Human Capital Theory, the study used a descriptive-correlational research design. Data were gathered from guidance designates assigned in 31 public secondary schools through a researcher-developed survey questionnaire validated by three Registered Guidance Counselors. The data were analyzed using frequency, percentage distribution, weighted mean, and multiple regression analysis at the 0.05 level of significance. Findings showed that most respondents held Bachelor’s Degrees, had served as guidance designates for seven years or more, and had attended limited guidance-related trainings. They were highly competent in interpersonal communication and crisis management but only moderately competent in program development, implementation, and assessment. Guidance services were generally highly implemented, particularly career guidance, prevention and intervention, orientation and information, individual inventory, follow up, and assessment and referral, while homeroom guidance was moderately implemented. Professional qualifications did not significantly predict the extent of guidance service implementation, but competencies significantly influenced implementation, with program development, implementation, and assessment emerging as the strongest predictor. The study concluded that formal qualifications provide a foundation, but competencies more directly determine effective service delivery. It recommends specialized capacity-building, mentorship, workload support, standardized tools, and stronger monitoring systems. The study supports SDG 3, SDG 4, SDG 8, SDG 16, and SDG 17 by strengthening school-based mental health support, quality education, career readiness, safer institutions, and stakeholder collaboration. Its sustainability impact lies in improving institutional capacity, educational support systems, public health response, and community-based learner welfare services.